A single nucleotide polymorphism in BCAT1 gene is associated with type 2 diabetes mellitus - Alfaqih, Mahmoud A.; Abu-Khdair, Zaina E.; Khabour, Omar; Kheirallah, Khalid A.; Khanfar, Mariam (Acta biochimica Polonica, 2021)
The level of circulatory branched chain amino acids (BCAAs) is often increased in type 2 diabetes mellitus (T2DM). Catabolism of BCAAs involves a transamination reaction mediated by the branched chain amino acid aminotransferase (BCAT1) enzyme. Differences in the level of BCAT1 were found to be linked with hypertension, obesity, and cancer. Herein, using a case control design, we tested the association of rs9668920 and rs12321766 polymorphisms in BCAT1 gene with T2DM. Three hundred subjects were recruited in the study. Genotyping of the indicated polymorphisms was achieved using restriction fragment length polymorphism technique after amplification of the target sequences. The results showed that, under a recessive inheritance model, the GG genotype of rs9668920 increased the risk of T2DM (P=0.026; OR 2.60; 95% CI 1.119–6.048). This effect was independent of the age, body mass index, waist circumference, serum glucose, cholesterol, triglycerides, and BCAAs (P>0.05). In conclusion, The GG genotype of BCAT1 rs9668920 SNP might be a risk factor of T2DM. More studies are required to confirm this finding.